Commuting Toeplitz and Hankel Operators on Harmonic Dirichlet Spaces. (13th April 2017) - Ding, Qian; Chen, Yong; Lu, Yufeng
Abstract : On the harmonic Dirichlet space of the unit disk, the commutativity of Toeplitz and Hankel operators is studied. We obtain characterizations of commuting Toeplitz and Hankel operators and essentially commuting (semicommuting) Toeplitz and Hankel operators with general symbols.